2017
DOI: 10.4103/1735-9066.212985
|View full text |Cite
|
Sign up to set email alerts
|

Effect of family–patient communication on the incidence of delirium in hospitalized patients in cardiovascular surgery ICU

Abstract: Background:Cardiovascular diseases are the most important causes of morbidity and mortality in the world, and cardiac surgery is one of the treatments that have complication for patients. One of the most important current psychological complications after cardiac surgery is delirium. For its prevention and treatment, considerable attention should be paid to the role of family. This study has been conducted for assessing the effect of the relationship between the family and patient on the incidence of delirium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
32
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 13 publications
(11 reference statements)
2
32
0
1
Order By: Relevance
“…Additionally, the presence of family at bedside for > 2 hours per day (reported as family engagement) was identi ed as a potential mitigating factor for ICU delirium this study, similar to other published reports [80,81]. This raises questions about the role that family may play in the care of a critically-ill loved one and presents an opportunity for inquiry as ICU visitation policies have been restricted in many cases during the current COVID-19 pandemic.…”
Section: Discussionsupporting
confidence: 81%
“…Additionally, the presence of family at bedside for > 2 hours per day (reported as family engagement) was identi ed as a potential mitigating factor for ICU delirium this study, similar to other published reports [80,81]. This raises questions about the role that family may play in the care of a critically-ill loved one and presents an opportunity for inquiry as ICU visitation policies have been restricted in many cases during the current COVID-19 pandemic.…”
Section: Discussionsupporting
confidence: 81%
“… 6 Moreover, some studies suggest the potential role of presence of family members as a strategy to prevent ICU delirium. 15–17 One small prospective single-centre before-and-after study found a reduction of 50% in the cumulative incidence of delirium by changing the visitation policy from a restrictive model (4.5 hours/day) to an extended model (12 hours/day); the length of delirium and ICU stay was also reduced in this study. 12 In this regard, the presence of family in the critical care setting is suggested as a means to achieve better pain control, reduce the use of sedatives and participate in the reorientation and cognitive stimulation of patients.…”
Section: Introductionmentioning
confidence: 53%
“…In relation to the risk of infection, this topic has been evaluated by few underpowered studies. 7 12 15 Although one study 15 showed greater environmental microbial contamination during an open policy of ICU visitation, published studies 7 12 15 failed to show an association between flexible ICU visiting hours and nosocomial infection. Lastly, the impact of flexible ICU visiting hours on symptoms of anxiety and depression of family members is not well studied: there is plausibility for decreased anxiety and depression with flexible ICU visiting hours as a result of improved access to information and more effective sharing of the decision-making process 24 ; conversely, it is also plausible to assume that anxiety and depression will increase as a result of higher exposure of family members to complex situations such as terminality and the patient’s emotional and physical suffering.…”
Section: Introductionmentioning
confidence: 99%
“…[10] Also a study conducted by Eghbali-Babadi et al, 2017 highlighted the importance of effective communication between the patient and the family as a non-medical management method which really reduced the occurrence of delirium after cardiac surgery. [25] Another study done by Birge A and Aydin H (2019) concluded that nurses' ability to perform non-pharmacological intervention orientation by supporting visits from family and friends was effective in reducing the incidence of delirium. This describes the role of the family participation in patient management to preventing complications following ICU admission.…”
Section: Discussionmentioning
confidence: 99%
“…[24] In addition, family-patient communication as a management strategy is proven to reduce the incidence of delirium. [25] International guidelines and protocols have new recommendations proposing changes in the way of the care delivered, challenging old paradigms and illuminating new unanswered questions that suggest the need for further research. Many studies focus on pharmacologic treatment of delirium while the effect of non-pharmacologic strategies has very few studies.…”
Section: Introductionmentioning
confidence: 99%